Piezoelectric behavior of SrRuO(3) buffered lanthanum modified bismuth ferrite thin films grown by chemical method - Simões, Alexandre Zirpoli [UNESP]; Gonzalez, A. H. M. [UNESP]; Aguiar, E. C. [UNESP]; Riccardi, C. S. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (American Institute of Physics (AIP), 2008)
Lanthanum modified bismuth ferrite thin film (BLFO) of pure perovskite phase was deposited on SrRuO(3)-buffered Pt/TiO(2)/SiO(2)/Si (100) substrates by soft chemical method. (111)-preferred oriented BLFO film was coherently grown at a temperature of 500 degrees C. The crystal structure of the film was characterized by using x-ray diffraction. The spontaneous polarization of the film was 25 mu C/cm(2). The film has a piezoelectric coefficient d(33) equal to 85 pm/V and a weak pulse width dependence indicating intrinsic ferroelectricity. Retention measurement showed no decay of polarization while piezoelectric response was greatly improved by the conductor electrode. (C) 2008 American Institute of Physics. [DOI: 10.1063/1.2979692]